First medical students’ protest in Peru - Zarate, Eduardo (2004)
The early years of the Peruvian Republic (1821 – 1830) were characterized by continuous civil wars and international conflicts that stalled agriculture and commerce and originated a serious fiscal crisis. With this social environment frame, the College of Medicine suffered a serious crisis with shut-down periods and changes in academic programs. Within this context, an unpublished manuscript on the first medical students’ civil protest was presented in 1829. The claims refered to academic issues and better learning conditions, claims unattended by the College authorities.